Differences in Satisfaction of Type 2 Diabetes Sufferers with the Android-Based WatDiab Application - Suyanto; Astuti, Sri Lestari Dwi (Postgraduate, University of Mataram, 2024)
The Covid 19 pandemic has forced nursing services to adapt, such as using smartphones containing applications for diabetes sufferers. The shortcomings of existing applications need to be improved to satisfy users. For this reason, the WatDiab application was designed in this research. The research design uses a comparative design to see the satisfaction of application users who live in cities and villages. Sampling using a purposive technique resulted in 140 respondents consisting of respondents who lived in the city and village. Data analysis uses Chi Square to assess differences in satisfaction with using the WatDiab application based on place of residence, education level and age group. The results showed that there were differences in user satisfaction based on education level (p value 0.002<0.05) and also based on age group (p value 0.018<0.05). Meanwhile, based on area of ​​residence, there was no difference in satisfaction (p value 0.545 > 0.05). In conclusion, there are differences in satisfaction based on education level and age group, while there are no differences based on area of ​​residence. Suggestion, there needs to be a review of the WatDiab application so that it can satisfy all age levels and levels of education who use it.